2020
DOI: 10.1002/sej.1368
|View full text |Cite
|
Sign up to set email alerts
|

Natural disasters as a source of entrepreneurial opportunity: Family business resilience after an earthquake

Abstract: Research Summary: What type of firms are more likely to survive or even thrive in disaster events such as earthquakes, wildfires, and the COVID-19 pandemic? We investigate whether family ownership and industry positioning affect firms' ability to capture opportunities for business recovery after a natural disaster. We analyze the performance of Italian family and nonfamily firms around a disastrous earthquake in 2009. Following the earthquake, family firms performed better than nonfamily firms, especially when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 128 publications
(206 reference statements)
3
102
4
1
Order By: Relevance
“…Our fourth hypothesis stated that COVID-19 interruptions are perceived as more severe by family firms. However, this hypothesis found no support and provides empirical evidence that does not support the view that family firms differ from non-family ones if the crisis or resilience to shock is considered, which is contrary to the findings of a more et al (2021), Salvato et al (2020), andSoluk et al (2021). First, we observed that statistically significant differences were confirmed between family and non-family firms only in the case of the perception of limited availability of workers and ability to continue production.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our fourth hypothesis stated that COVID-19 interruptions are perceived as more severe by family firms. However, this hypothesis found no support and provides empirical evidence that does not support the view that family firms differ from non-family ones if the crisis or resilience to shock is considered, which is contrary to the findings of a more et al (2021), Salvato et al (2020), andSoluk et al (2021). First, we observed that statistically significant differences were confirmed between family and non-family firms only in the case of the perception of limited availability of workers and ability to continue production.…”
Section: Discussioncontrasting
confidence: 99%
“…Arregle et al (2007) suggested that the presence of a family in the business is assumed to ensure stable and trusting long-lasting relationships with external and internal actors, accruing distinctive social capital. Additionally, Salvato et al (2020) proved that the superior resilience of family firms was linked to the ability to seize posttraumatic entrepreneurial opportunities for recovery and growth.…”
Section: Family Ownershipmentioning
confidence: 99%
“…Similar research projects may bring a connection between the macro political economy of the disasters and their results at the micro level of affected populations and related family/household businesses. Importantly, the above research touches the pivotal topic of the recovery phase of natural disasters because the economic re-launch and resilience of businesses, territories and populations ravaged by massive natural calamities have been on the agenda of prior governments and contemporary societies (Salvato et al, 2020). Examples can be drawn mainly from twentieth century disasters in developed and developing countries (Albala-Bertrand, 1993).…”
Section: Looking For Disasters' Foci and Locimentioning
confidence: 99%
“…As this context suggests, natural disasters often result in emergencies that dramatically affect firms' economic environments. Such disasters create unexpected, localized, and exogenous distress to economic circumstances and, therefore, greatly affect how firms operate (Salvato et al, 2020). In the setting of our study, Rumbia provided an opportunity to explore the role of LM and AMTs in mass emergencies.…”
Section: The Context Of the Studymentioning
confidence: 99%